Designing a multi-epitope vaccine against coxsackievirus B based on immunoinformatics approaches - Huang, Sichao; Zhang, Congcong; Li, Jianing; Dai, Zongmao; Huang, Jingjing; Deng, Fengzhen; Wang, Xumeng; Yue, Xinxin; Hu, Xinnan; Li, Yuxuan; Deng, Yushu; Wang, Yanhang; et al. (Frontiers in Immunology, 2022)
Coxsackievirus B (CVB) is one of the major viral pathogens of human myocarditis and cardiomyopathy without any effective preventive measure, therefore, it is necessary to develop a safe and efficacious vaccine against CVB. Immunoinformatics methods are both economical and convenient, as in silico simulations can shorten the development time. Herein, we design a novel multi-epitope vaccine for the prevention of CVB by using immunoinformatics methods. With the help of advanced immunoinformatics approaches, we predicted different B-cell, cytotoxic T lymphocytes (CTL), and helper T lymphocytes (HTL) epitopes, respectively. Subsequently, we constructed the multi-epitope vaccine by fusing all conserved epitopes with appropriate linkers and adjuvants. The final vaccine was found to be antigenic, non-allergenic and stable. The 3D structure of the vaccine was then predicted, refined, and evaluated. Molecular docking and dynamics simulation was performed to reveal the interactions between the vaccine with immune receptors TLR-3, MHC-I, and MHC-II. Finally, to ensure the complete expression of the vaccine protein, the sequence of the designed vaccine was optimized and further performed in silico cloning. In conclusion, the molecule designed in this study could be considered as a potential vaccine against CVB infection and needed further experimental to evaluate its safety and efficacy.